Non-Pharmacological Management of Nausea and Vomiting in Cancer: A Scoping Review - Santi Wahyuningsih; Yati Afiyanti; Agung Waluyo; Margaret I Fitch (Jurnal Keperawatan Indonesia, 2023)
Prevention and management of nausea and vomiting are important in cancer treatment. Effective management requires both pharmacological and non-pharmacological interventions. Patients and family members have important contributions to achieve effective control of nausea and vomiting through self-management. The objective of this review is to explore and synthesize the scientific literature about self-management strategies as a type of non-pharmacological intervention for managing nausea and vomiting in cancer patients. The articles were searched in PubMed, Science Direct and ClinicalKey databases using keyword combinations of "cancer", “non-pharmacological”, "intervention", "management", "nausea" and "vomiting". The inclusion criteria were articles that were free; full text; published in the last five years; provided information about non-pharmacological strategies in managing nausea and vomiting in cancer; and were written in English. Out of a total of 232 papers identified, 21 were selected. The results show that non-pharmacological management of nausea and vomiting ranged from simple self-management techniques to integrative therapies and palliative interventions. Self-management emphasizes patient autonomy in their own care and encourages patients and families to assume the responsibility of managing relevant aspects of their condition. The strategies include dietary modifications, environmental modifications, psychological strategies, exercise and taking of medication as prescribed. The interventions discussed in this article can be applied by patients as directed or instructed by healthcare teams. Nurses play an important role in educating patients on non-pharmacological interventions and encouraging them to achieve self-efficacy. Further research of other such interventions with larger sample sizes is needed to provide more accurate results.   Abstrak Manajemen Nonfarmakologis Mual dan Muntah pada Kanker: Scoping Review. Pencegahan dan pengelolaan mual dan muntah penting dalam pengobatan kanker, yang efektif dengan intervensi farmakologis dan nonfarmakologis. Pasien dan anggota keluarga pun mempunyai kontribusi penting untuk mencapai pengendalian mual dan muntah yang efektif melalui manajemen diri pasien. Tujuan dari tinjauan ini adalah untuk mengeksplorasi dan menyintesis literatur ilmiah tentang strategi manajemen diri sebagai jenis intervensi nonfarmakologis untuk mengelola mual dan muntah pada pasien kanker. Artikel-artikel tersebut dicari di basis data PubMed, Science Direct, dan ClinicalKey menggunakan kombinasi kata kunci "kanker", "non-farmakologis", "intervensi", "manajemen", "mual", dan "muntah" dengan kriteria inklusi seperti: artikel tidak berbayar; teks lengkap; diterbitkan dalam lima tahun terakhir; memberikan informasi tentang strategi non farmakologis dalam manajemen mual muntah pada pasien kanker; dan ditulis dalam Bahasa Inggris. Dari total 232 makalah yang diidentifikasi, 21 dipilih untuk penelitian ini. Hasil telaah menunjukkan bahwa manajemen nonfarmakologis mual dan muntah meliputi teknik manajemen diri yang sederhana hingga terapi integratif dan intervensi paliatif. Manajemen diri menekankan otonomi pasien dalam perawatan mandiri dengan mendorong pasien dan keluarga untuk bertanggung jawab mengelola aspek yang relevan dari kondisi mereka. Strategi tersebut meliputi modifikasi pola makan, modifikasi lingkungan, strategi psikologis, olahraga, dan minum obat sesuai resep. Intervensi yang dibahas dalam artikel ini dapat diterapkan oleh pasien seperti yang diarahkan atau diinstruksikan oleh tim kesehatan. Perawat memainkan peran penting dalam mendidik pasien tentang intervensi nonfarmakologis dan mendorong mereka untuk mencapai efikasi diri. Penelitian lebih lanjut dari intervensi serupa lainnya dengan ukuran sampel yang lebih besar diperlukan untuk memberikan hasil yang lebih akurat. Kata Kunci: intervensi, kanker, manajemen, mual, muntah, nonfarmakologis